L’utilità di un approccio integrato nella didattica della chimica - Domenici, Valentina (Chimica nella Scuola, 2024)
This is a brief report of my experiences as teacher of chemistry education and other chemistry-related subjects at the University of Pisa. The educational approach here described is an integrated teaching method where several active methodologies, such as the cooperative learning and project-based learning, are used together with the epistemological/historical approach in the frame of the STEAM teaching philosophy.